SUMBER MODAL PADA USAHA KECIL MAKANAN RINGAN DESA KELANGONAN GRESIK - Ely Safanah (Jurnal Riset Entrepreneurship, 2018)
This study aims to describe the essence of the meaning of the source of small-business snack food Village Kelangonan Gresik. This research is a qualitative type research. The object of this research is in Kelangonan Gresik Village. This research can be categorized in an interactive qualitative method which is an in-depth study using direct data collection techniques from people in their natural environment. Technique of extracting data in this research by interview. The conclusions of this study are self-capital and related accounts. The relationship between accounts receivable and capital itself is encouraged or reinforced by cash.